Las medidas de aguas en el México colonial: unidades, su manejo y legislación al respecto - Laserna Gaitán, Antonio Ignacio (Chronica Nova. Revista de Historia Moderna de la Universidad de Granada)
The geographer Guy Lasserre once commented that what most surprised him was not the aridity of the majority of the Mexican territory but rather that a “green Mexico” even existed. Ever since Pre-Columbian times, the inhabitants of this country have dedicated a great deal of time to the rationing and distribution of the region’s precious hydric resources. During the Spanish colonization substantial efforts were also made in this direction. According to Sáenz de Escobar, author of the treaty which is used as a basic point of reference for this article, the first step to be taken when attempting to distribute water is to measure the sources and make calculations for their possible division. The present study constitutes a means of familiarization with the units of measure and forms of distribution of Mexican water during the period of Spanish colonization, and includes mention of the tools used to build waterways and fountains as well as the principles of legislation and common sense that should accompany work of this sort.